Biopolymers for Antitumor Implantable Drug Delivery Systems Recent Advances and Future Outlook - Talebian, Sepehr (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.